Prohibition Of Exporting Nickel Ore To The European Union In International Trade Law Perspective - Dinda Dwi Putri (Activa Yuris: Jurnal Hukum, 2021)
Indonesia accelerated the prohibition on nickel ore exports which previously was enforced in 2022 and accelerated to 2020. The European Union feels that it has been greatly disadvantaged from the Indonesian government's policies so the European Union sued to the WTO with complaint number Ds592. This study aims to analyze and explain Indonesia's dispute with the European Union regarding the prohibition on nickel ore exports to the European Union in 2020. This article aims to determine the challenges and efforts of the Indonesian government in dealing with nickel ore disputes with the European Union. The results of the research here show that Indonesia will not be afraid to face the dispute between Indonesia and Europe Union and Indonesia has prepared quite strong files in terms of these suits